CHARACTERISTICS OF MOVEMENTS WHEN CYLINDRICAL TURNING, DRILLING, COREDRILLING AND REAMING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the process of work the tool angles change their value to become the working angles. This results in a variation of the work conditions of the cutting tools. The variation depends on the characteristic of the resultant cutting motion – the sum of the cutting motion and feed motion.In this article the characteristics of motions of cylindrical turning, drilling, coredrilling and reaming are derived, which can serve as a basis for determining the relations between the tool and working angles. These relations can be used in programming the CNC to prevent the formation of negative working clearance angle and the destruction of the tool.